1996
DOI: 10.1002/(sici)1098-1004(1996)7:3<244::aid-humu9>3.3.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Cystic fibrosis mutation detection by hybridization to light‐generated DNA probe arrays

Abstract: We have combined photochemistry and photolithography with solid-phase DNA synthesis chemistry to form a new technology that makes high density oligonucleotide probe array synthesis possible. Hybridization to these two-dimensional arrays containing hundreds or thousands of oligonucleotide probes provides a powerful DNA sequence analysis tool. Two types of light-generated DNA probe arrays have been used to test for a variety of mutations in the cystic fibrosis transmembrane conductance regulator (CFTR) gene. One… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 10 publications
0
15
0
1
Order By: Relevance
“…While many of these mutations are extremely rare and not all mutations are disease-causing, there is a clear need for a novel platform for genetic testing of CF which can provide simultaneous screening of a large proportion of CFTR mutations with a high level of accuracy and precision, affordable cost, and which would be compatible with a high throughput screening programme [5]. DNA microarray platforms have been developed using different approaches to implement mutation detection [3,6,7], and thus the potential exists for such platforms to provide a complete solution to CFTR mutation detection for CF screening.…”
Section: Introductionmentioning
confidence: 99%
“…While many of these mutations are extremely rare and not all mutations are disease-causing, there is a clear need for a novel platform for genetic testing of CF which can provide simultaneous screening of a large proportion of CFTR mutations with a high level of accuracy and precision, affordable cost, and which would be compatible with a high throughput screening programme [5]. DNA microarray platforms have been developed using different approaches to implement mutation detection [3,6,7], and thus the potential exists for such platforms to provide a complete solution to CFTR mutation detection for CF screening.…”
Section: Introductionmentioning
confidence: 99%
“…Of 48 markers that did not display discrimination, 45 (94%) were shown to have been sequenced correctly, confirming that failure of markers is attributable to lack of discrimination by the array. It has been shown that more extensive optimization of conditions and array design will increase the percentage of functional markers; however, sufficient markers displayed discrimination for the purposes of this study 18 .…”
mentioning
confidence: 99%
“…Replacement of 32% dTTPs with dUTP, which generated DNA templates of 50-150 bp, was optimal in this APEX study. Most studies have used 20% dUTP [25][26][27][28][29]. There was only one study that used 15% dUTP [37] in the PCR reaction.…”
Section: Apex Detection In Blind Dna Samplesmentioning
confidence: 80%
“…Before adding to the APEX reaction, the PCR products were digested into smaller fragments using uracil Nglycosylase and heat treatment. This enzyme specifically hydrolyzes the N-glycosilic bond connecting uracil to the deoxyribose sugar and generates abasic sites in DNA [25]. After digestion, 100-300 bp and Table 3 List of forty-eight genotypes from eight DNA samples detectable with the APEX microarray.…”
Section: Uniplex Pcr Purification and Fragmentation Of Pcr Productsmentioning
confidence: 99%
See 1 more Smart Citation